(untitled) - Cotterell, Arthur (London, 1993)
This is a welcome revised edition of a set of thumbnail sketches, originally published in 1993, of the history of China, Japan and every country in south-east Asia. The author blends history and legend skilfully, showing how much national feeling reveres legend, while making clear what is truth and what is fancy. He displays the ancient strength and later weakness of China, and the rapacity of the European merchants who sought to exploit this weakness, as well as the incursions of the Americans into Japan and the Philippines, also motivated largely by the desire for profit. He discusses the successive incursions of Buddhism, Islam, the Mongols and Christianity, remarking for instance on the disappointment of American Protestant missionaries who went to the newly conquered Philippines, only to find that under Spanish pressure the inhabitants had long since become Roman Catholics. He notices the importance of the Japanese conquest of Malaya and Indonesia in 1941-2 as a spur towards national independence; and summarizes the military interventions - Japanese and other - on the Chinese mainland. He heads a new concluding chapter for this enlarged edition 'The Pacific Millennium: A Return to Chinese Leadership'. In it he discusses the banking crises of the 1990s, the excision of East Timor from Indonesia, the recurring difficulties between China and Taiwan, the importance of relations between China and the USA, and the emergence of China as the dominant power on the Pacific Rim. This is an invaluable handbook for anyone studying the area. (Kirkus UK)
Keywords: Kinh tế chính trị Đông Á